Salvianolic Acid B Inhibits Activation of Human Primary Hepatic Stellate Cells Through Downregulation of the Myocyte Enhancer Factor 2 Signaling Pathway - Zhang, Wenwei; Ping, Jian; Zhou, Yang; Chen, Gaofeng; Xu, Lieming (Frontiers in Pharmacology, 2019)
Various isoforms of myocyte enhancer factor 2 (MEF2) have been shown to play a role in the activation of rat hepatic stellate cells (HSCs) in culture. What signals regulate MEF2 in HSCs is unknown. In addition, whether MEF2s regulate the activation of human liver HSCs (H-HSCs) is not clear. Here we studied the expression and function of MEF2 in H-HSCs. Our data showed that the levels of MEF2A, C, and D proteins are high in liver tissues from patients with cirrhosis and increase during culture-induced activation of primary H-HSCs. Exposure of H-HSCs to TGF-1 led to significant increase in MEF2A and C protein levels and enhanced MEF2 activity. Interestingly, TGF-1 did not further enhance the level of MEF2D. TGF-1 activated p38 MPAK and led to increased phosphorylation of MEF2C at its p38 recognition site. Inhibition of p38 MAPK inhibited both TGF-1 and culture-induced activation of MEF2. Over-expression of dominant negative MEF2 mutants that are either resistant to phosphorylation by p38 or block DNA binding reduced Col I reporter activity in H-HSCs. Salianic-acid B (SA-B), a water-soluble element of Radix Salviae Miltiorrhizae known to have anti-fibrosis effect, attenuated both basal and TGF-1-induced increase in levels of MEF2A and C mRNA and protein. SA-B inhibited MEF2 activity, which correlated with reduced expression of HSC activation markers -SMA and Col I. SA-B administration reduced MEF2A in vivo, which is accompanied by reduced level of -SMA in a model of DMN-induced rat liver fibrosis. It comes the conclusion that MEF2 transcription factor was stimulated by TGF1 in H-HSC, antagonizing TGF1 induced activation of MEF2 signal pathway may account for part of SA-B anti-fibrosis action.